Chronos in Aristotle’s Physics - Harry, Chelsea C. author. aut Link
XIX, 75 p.
Keywords: This book is a contribution both to Aristotle studies and to the philosophy of nature, and not only offers a thorough text based account of time as modally potentiality in Aristotle’s account, but also clarifies the process of “actualizing time” as taking time and looks at the implications of conceiving a world without actual time. It speaks to the resurgence of interest in Aristotle’s natural philosophy and will become an important resource for anyone interested in Aristotle’s theory of time, of its relationship to Aristotle’s larger project in the Physics, and to time’s place in the broader scope of Aristotelian natural science. Graduate students and scholars researching in this area especially will find the authors arguments provocative, a welcome addition to other recent publications on Aristotle’s Treatise on Time.